The Influence of Madrasah Principal Leadership and Work Environment on Madrasah Teacher Performance - Halik, Sampara; Yunus, Abdul Rahim; Semmaila, Baharuddin; Syahid, Akhmad; Asykur, Muamar (JURNAL AL-TANZIM, 2022)
This study aims to test and analyze about; 1) the influence of principal madrasah leadership on teacher performance; 2) the influence of the work environment on teacher performance; 3) the influence of leadership and work environment together on teacher performance. This study uses primary data through a questionnaire of as many as 391 teacher respondents as a sample of the total number of teachers, as many as 1,790 teachers spread from all Madrasah Aliyah Negeri in South Sulawesi. The results show that together the two independent variables, namely: leadership (X1) and the work environment (X2), have a positive and significant influence on teacher performance (Y) which can be shown by the value of F count = 30,872 and Probability (sig) = 0.000 < = 0.05. While the contribution or contribution of the influence of the two independent variables is relatively significant, namely: leadership (X1) and work environment (X2) on teacher performance which can be shown through the value of the determination index (R2) = 0.637 or 63.70% variation in teacher performance and there are 0.363 or 36.30% teacher performance is determined by other factors not included in this study.